DEIXIS IN DONALD TRUMPâ€™S SPEECH TO UN GENERAL ASSEMBLY - Retnowaty, Retnowaty (English Department FBS UNP, 2019)
The objective of the study is â€œto describe how deixis are used in Donald Trumpâ€™s Speech to UN General Assemblyâ€. The design of this study is a descriptive qualitative design. Source of data collection in this research is the text of Donald Trumpâ€™s Speech to UN General Assembly done in 2018. After collecting data, the researcher found and selected data that the most of sentences or words have deixis types. After the data were reduced, then the next step is to display data, then, presenting data. Data summarizing was a means to know the result of the study. Here, the researcher made conclusion after completely identifying and analyzing the types of deixis and the most dominant one found in the speech. Based on data analysis, the researcher found five kinds of deixis in Donald Trumpâ€™s Speech to UN General Assembly, they are person deixis, spatial/place deixis, temporal/time deixis, discourse deixis and social deixis. The total number of deixis in this speech are 344 utterances. The deixis that mostly used by the Donald Trump is the person deixis with the frequency of 279 (81.10%).Keywords: